MIKRO SILIKA SEBAGAI BAHAN TAMBAH UNTUK MENINGKATKAN KUAT TEKAN BETON MUTU TINGGI - Mahyar, Herri (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI TERAPAN "REINTEK" (REKAYASA INOVASI TEKNOLOGI), 2012)
High Quality concrete have used as many last construction material for a number of years by using is assorted of materials add. high Quality concrete classified as concrete with high strength ( bigger than 400 singk / cm2 ) . Intention of this research that is to be is optimal of strength depress high quality concrete with materials growing microly of type silica of sikafume. Result of research indicate that by enhancing is micro of type silica of sikafume, strong depress tired concrete 743,10 singk / cm2.